Influence of Uterine Anomalies, Infection History, and Cervical Length on the Success of Cerclage in First-Time Pregnancies - Ayesha Saddiqa; Ayesha; Abeera Khalid; Nosheen Fatima; Hira Khalid; Syed Muntzir Mehdi; Pakeeza Shafique Ul Rehman (Pakistan Journal of Medicine and Dentistry)
Background: Cervical cerclage is an important procedure that helps keep pregnancies from ending prematurely in women with cervical weakness. So far, not much is known about how uterine abnormalities, infection background and cervical length affect the outcomes of cerclage surgery in first-time mothers. The aim of the study was to find out if uterine abnormalities, infection history and a short cervix influenced cerclage outcomes in single pregnancies.